The Website-Based Information System Design At Cahaya Harapan Jaya Building Shop - Sutrisno, Iwan; Sudarmilah, Endah (Information Technology and Science (ITScience), 2025)
Building material stores play an important role in providing building materials, but many still rely on conventional management systems that are less efficient in recording stock, transactions, and employee data. This results in delays in recording transactions, errors in stock monitoring, and the lack of an effective system in managing employee data. Therefore, this study aims to design a web-based information system to improve the operational efficiency of building material stores. This study uses the Waterfall method which consists of needs analysis, design, programming, testing and implementation of this system also uses blackbox testing and system usability scale (SUS) testing. This system is designed to make it easier for administrators and employees to manage products, transactions, employee data, and financial reports in real-time. The results of the study show that the web-based information system improves the efficiency of transaction recording, minimizes stock monitoring errors, and simplifies the management of employee data and financial reports. This system allows building material stores to optimize operational performance, improve data accuracy, and provide better customer service.